Progression of nurses within the NHS - George Stoye; Max Warner (Institute for Fiscal Studies (IFS), 2024)
In this report, we examine the career progression of nurses and other staff groups within the NHS Agenda for Change (AfC) pay framework in England over the decade between 2012 and 2021. We document differences in progression across pay bands between staff groups and within groups of nurses to provide important context when considering how - and why - the career progression of nurses needs to be reformed.
Keywords: 330; Health and social care; Employment; Labour supply and workforce; NHS; Healthcare